DEVELOPMENT OF HYBRID ELECTRICAL VEHICLE CHARGING STATION - Etaktpure Gayatri, Kale Sakshi, Sawant Kishori, Dhole Vaishnavi; Tekale Anil (International Journal of Innovations in Engineering Research and Technology, 2022)
Electric vehicles have become a major trend in the development of the automobile industry. Most sources of non-renewable energy are fossil fuels. Nowadays cost of petrol and diesel are increasing. Non-renewable Sources are limited. In order to making charging station for E-vehicles, it will sustain if they are made from nonrenewable sources. So that we are making a hybrid charging station using renewable sources like solar and wind. Electrical vehicles are fast becoming a popular site in the world. Their technologies have been widely developed over the years. However, their charging infrastructure is still a subject of interest, as most of the electric vehicle charging requirements were previously met by an AC grid. However, over the year's research has been conducted on the implementation of renewable energies in the charging station. Most of the research studies focus on the management, optimal control, charging schemes and charging strategies. There is no research done on a charging station that combines the grid integrated hybrid renewable energy system such as Wind and PV comprising of a central battery bank with a peer-to-peer energy trading model. The aim of this project is to develop a well-coordinated charging scheme of Electric vehicles in a charging station whilst optimally managing the charging and discharging of the central battery bank (used for energy storage) as well as the power dispatch of the grid and Wind and PV charging station. The proposed model will maximize electrical vehicle user satisfaction that meets all the charging requirements of the charging station